tḥfīz ālʿṣb ālrāʾsī ālʿāšr bīn ālṭrq ālṭbīa ālṭbīʿīa ūālqrāʾān ūālsna ālnbūīa ūālmmārsāt ālāʾslāmīa = Vagus Nerve Stimulation between Natural Medical Procedures and the Quran, Prophetic Traditions and Islamic Practices - Al-Alami, Zina M. (Al-Bayān, 2021)
Abstract Vagus nerve (the tenth cranial nerve), is responsible for several vital physiological conditions and several motor and sensory actions in the thoracic and abdominal cavities. Because of its importance, scientists usually stimulate it electrically in certain medical conditions, or naturally for the wellbeing of individuals. The aim of this study is to compare between the natural ways that stimulate the vagus nerve, that were suggested by anatomists, physiologists and medical doctors, and between what it is mentioned in the Quran and Sunnah and practiced by Muslims. The study found that many of the documented natural practices that stimulate the vagus nerve are actually mentioned in the Quran or Sunnah. We concluded that some natural methods of vagus nerve stimulation are mentioned in many Islamic textual sources and Islamic practices.